A multi-species synthesis of satellite telemetry data in the Pacific Arctic (1987–2015): Overlap of marine mammal distributions and core use areas. (June 2018) - Citta, John J.; Lowry, Lloyd F.; Quakenbush, Lori T.; Kelly, Brendan P.; Fischbach, Anthony S.; London, Josh M.; Jay, Chadwick V.; Frost, Kathryn J.; Crowe, Gregory O'Corry; Crawford, Justin A.; Boveng, Peter L.; Cameron, Michael; et al.
Abstract: We collated available satellite telemetry data for six species of ice-associated marine mammals in the Pacific Arctic: ringed seals ( Pusa hispida ; n  = 118), bearded seals ( Erignathus barbatus, n  = 51), spotted seals ( Phoca largha, n  = 72), Pacific walruses ( Odobenus rosmarus divergens, n  = 389); bowhead whales ( Balaena mysticetus, n  = 46), and five Arctic and sub-arctic stocks of beluga whales ( Delphinapterus leucas, n  = 103). We also included one seasonal resident, eastern North Pacific gray whales ( Eschrichtius robustus, n  = 12). This review summarized the distribution of daily locations from satellite-linked transmitters during two analysis periods, summer (May–November) and winter (December–April), and then examined the overlap among species. Six multi-species core use areas were identified during the summer period: 1) Chukotka/Bering Strait; 2) Norton Sound; 3) Kotzebue Sound; 4) the northeastern Chukchi Sea; 5) Mackenzie River Delta/Amundsen Gulf; and 6) Viscount Melville Sound. During the winter period, we identified four multi-species core use areas: 1) Anadyr Gulf/Strait; 2) central Bering Sea; 3) Nunivak Island; and 4) Bristol Bay. During the summer period, four of the six areas were centered on the greater Bering Strait region and the northwestern coast of Alaska and included most of the species we examined. The two remaining summer areas were in the western Canadian Arctic and were largely defined by the seasonal presence of Bering-Chukchi-Beaufort stock bowhead whales and Eastern Beaufort Sea stock beluga whales, whose distribution overlapped during both summer and winter periods. During the winter period, the main multi-species core use area was located near the Gulf of Anadyr and extended northwards through Anadyr and Bering Straits. This area is contained within the Bering Sea "green belt", an area of enhanced primary and secondary productivity in the Bering Sea. We also described available telemetry data and where they can be found as of 2017. These data are important for understanding ice-associated marine mammal movements and habitat use in the Pacific Arctic and should be archived, with appropriate metadata, to ensure they are available for future retrospective analyses.